MATH 100, Section 110 (CSP) Week 5: Marked Homework Solutions 2010 Oct 14 1. [3] Check that x = −1, y = −1 in fact satisfies the equation. Implicitly differentiating the equation gives d d −1 (y x) + 3(x−1 y)2 · (x−1 y) = 0, dx dx and then −y −2 y 0 x + y −1 + 3(x−1 y)2 (−x−2 y + x−1 y 0 ) = 0, or 1 3y 3 x 3y 2 − 4 + − 2 + 3 y 0 = 0. y x y x Substituting (x, y) = (−1, −1) we get 2 − 2y 0 = 0, so y 0 = 1 at the point (−1, −1), and an equation of the tangent line is y = −1 + 1 · (x + 1), or more simply y = x. 2. [3] Check that x = 1, y = 0 satisfies the equation. Implicit diffferentiation of the equation gives y 0 ex−1 + yex−1 + ey + xey y 0 = 0. Substituting (x, y) = (1, 0) gives 1 + 2y 0 = 0, so y0 = − 1 2 is the slope of the tangent line at (1, 0). 3. (a) [2] dx dt = −√ 1 1−(sin−1 t)2 · d dt sin−1 t 1 = −p . √ 1 − (sin−1 t)2 1 − t2 d ln[x2 + (x3 + x)1/2 ] = x2 +(x31+x)1/2 · 2x + 12 (x3 + x)−1/2 (3x2 + 1) (b) [2] dx 1 3x2 + 1 √ = · 2x + √ . x2 + x 3 + x 2 x3 + x (c) [4] Use logarithmic differentiation: Let y = f (x), then ln y = ln (xarctan x ) = arctan x ln x, dy dy 1 1 = 1+x (ln x) + (arctan x) x1 , solving for dx = f 0 (x) and using y = xarctan x we get 2 y dx 0 f (x) = x arctan x arctan x ln x + . 1 + x2 x 1 (d) [4] Use logarithmic differentiation: ln y = ln (cos x)sin x = sin x ln(cos x), dy sin x cos1 x (− sin x), solving for dx and using y = (cos x)sin x we get 1 dy y dx = cos x ln(cos x)+ dy = (cos x)sin x [cos x ln(cos x) − sin x tan x]. dx 4. [3] f (0) (x) = f (x) = ln(x/2) = ln x − ln 2 f (1) (x) = f 0 (x) = x1 = x−1 since ln 2 is a constant (or use the Chain Rule directly on ln(x/2)) f (2) (x) = f 00 (x) = (−1)x−2 f (3) (x) = f 000 (x) = (−1)(−2)x−3 f (4) (x) = f 0000 (x) = (−1)(−2)(−3)x−4 1 Following the pattern, f (101) (x) = (−1)(−2)(−3) · · · (−100)x−101 = 100! x101 , and therefore 1 (101) f (2) = 100! 2101 . 5. (a) [3] Differentiating the suggested function ψ(x) = C sin 2π x , we get (using the Chain λ 2 Rule) ψ 0 (x) = 2π C cos 2π x , and differentiating again we get ψ 00 (x) = − 4π C sin 2π x . λ λ λ2 λ Therefore 4π 2 4π 2 2π 00 ψ (x) = − 2 C sin x = − 2 ψ(x), λ λ λ which verifies that the suggested function is indeed a solution of the differential equation. Substituting x = 0 into the function ψ(x) gives ψ(0) = C sin 0 = 0, which verifies that the function also satisfies the first condition for any value of C. (b) [4] Substituting x = 1 into the function ψ(x) and its derivative ψ 0 (x) (calculated above) gives 2π 2π 2π 0 + C cos = C (sin X + X cos X), ψ(1) + ψ (1) = C sin λ λ λ where 2π λ 0 is positive. Therefore ψ(1) + ψ (1) = 0 for any value of C if and only if sin X + X cos X = 0 if and only if tan X = −X X= for X > 0. But by Question 2 of the Week 2: Marked Homework Assignment (see the graph on p. 2 of the Solutions), there are infinitely many positive values of X which satisfy this last equation, and therefore there are infinitely many values of λ = 2π such that ψ(x) = X 2π 0 C sin λ x satisfies the second condition ψ(1) + ψ (1) = 0 for any value of C. (Note that these values of λ are discrete, as in the “particle in a box” example, but in this case (due to the condition ψ(1) + ψ 0 (1) = 0), simple expressions for the exact values of λ cannot be found.) 2